LABORATORY-SCALE PRODUCTION OF ADU GELS BY EXTERNAL GELATION FOR AN INTERMEDIATE HTGR NUCLEAR - S Simbolon; S R Susilowati (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2015)
LABORATORY-SCALE PRODUCTION OF ADU GELS BY EXTERNAL GELATION FOR AN INTERMEDIATE HTGR NUCLEAR. The The aim of this research is to produce thousands of microsphere ADU (Ammonium Diuranate) gels by using external gelation for an intermediate HTGR (High Temperature Gas-cooled Reactor) nuclear fuel in laboratory-scale. Microsphere ADU gels were based on sol-solution which was made from a homogeneous mixture of ADUN (Acid Deficient Uranyl Nitrate) which was containing uranyl ion in high concentration, a water soluble organic compound PVA (Polyvinyl Alcohol) and THFA (Tetrahydrofurfuryl Alcohol). The simple unified home made laboratory experimental machine was developed to replace test tube experiment method which was once used due to a tiny amount of microsphere ADU gels produced. It consists of four main parts: tank filled sol-solution connecting to peristaltic pump and vibrating nozzle, preliminary gelation and gelation column. The machine has successfully converted 150 mL sol-solution into thousands of drops which produced 120 - 130 drops in each minute in steady state in ammonia gas free sector. Preliminary gelation reaction was carried out in ammonia gas sector where drops react with ammonia gas in a bat an eye followed by gelation reaction in column containing ammonia solution 7 M. In ageing process, ADU gels were collected and submerged into a vessel containing ammonia solution which was shaken for 1 hour in a shaker device. Isopropyl alcohol (90%) solution was used to wash ADU gels and a digital camera was used to measured spherical form of ADU gels. Diameters in spherical spheroid form were found between 1.8 mm until 2.2 mm. The spherical purity of ADU gels were 10% - 20% others were oblate, prolate spheroid and microsphere which have hugetiny of dimples on the surface. PRODUKSI GEL ADU SKALA LABORATORIUM DENGAN MENGGUNAKAN GELASI EKSTERNAL UNTUK BAHAN BAKAR ANTARA HTGR. Penelitian ini bertujuan untuk membuat ribuan gel bulat ADU (Ammonium Diuranate) dengan menggunakan gelasi ekternal untuk bahan bakar nuklir HTGR (High Temperature Gas-cooled Reactor) menengah untuk skala laboratorium.  Gel bulat ADU dibuat berbasis pada larutan-sol yang dibentuk dari campuran homogen ADUN (Acid Deficient Uranyl Nitrate) yang mengandung ion uranil dengan konsentrasi sangat tinggi, larutan PVA (Polyvinyl Alcohol) dan THFA (Tetrahydrofurfuryl Alcohol). Perangkat laboratorium untuk eksperimen dikembangkan untuk menggantikan metode eksperimen tabung pengujian yang telah digunakan untuk menghasilkan sejumlah gel bulat ADU.  Perangkat tersebut terdiri atas empat bagian utama: tangki yang berisi larutan-sol yang terhubung dengan pompa peristaltik dan nosel vibrasi, gelasi awal dan kolom gelasi.  Perangkat tersebut telah berhasil mengubah 150 mL larutan-sol menjadi ribuan tetes dengan produksinya berkisar 120-130 tetesan tiap menit dengan kondisi tunak dalam sektor yang bebas gas ammonia.  Reaksi awal gelasi dilakukan di sektor gas ammonia dimana tetesan bereaksi dengan gas amonia yang diikuti dengan reaksi gelasi di dalam kolom yang mengandung larutan ammonia 7 M.  Dalam proses penuaan, gel ADU ditampung dan direndam dengan larutan ammonia yang digoyang selama 1 jam.  Larutan isopropyl alkohol (90%) digunakan untuk mencuci gel ADU dan kamera digital digunakan untuk mengukur kebulatan gel ADU.  Diameter dari bentuk bulat bola  berkisar antara 1.8 mm hingga 2.2 mm.  kebulatan gel ADU selama produksi berkisar 10% - 20%, selain itu berbentuk bola oblate, prolate dan ada cekungan pada permukaan.